2022
DOI: 10.1111/nph.18548
|View full text |Cite
|
Sign up to set email alerts
|

Stemborer‐induced rice plant volatiles boost direct and indirect resistance in neighboring plants

Abstract: Summary Herbivore‐induced plant volatiles (HIPVs) are known to be perceived by neighboring plants, resulting in induction or priming of chemical defenses. There is little information on the defense responses that are triggered by these plant–plant interactions, and the phenomenon has rarely been studied in rice. Using chemical and molecular analyses in combination with insect behavioral and performance experiments, we studied how volatiles emitted by rice plants infested by the striped stemborer (SSB) Chilo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 71 publications
(128 reference statements)
0
7
0
Order By: Relevance
“…In spite of qualitative overlap between volatile blends of rice and sorghum (Table S1, Figures 3, 5 , S2), 13 , 34 , 35 significantly higher levels of induced VOCs were typical for rice. In addition, low levels of basal volatiles emitted from sorghum support the idea of sorghum being a low emitter rather than being a low responder to herbivory stimuli.…”
Section: Discussionmentioning
confidence: 97%
“…In spite of qualitative overlap between volatile blends of rice and sorghum (Table S1, Figures 3, 5 , S2), 13 , 34 , 35 significantly higher levels of induced VOCs were typical for rice. In addition, low levels of basal volatiles emitted from sorghum support the idea of sorghum being a low emitter rather than being a low responder to herbivory stimuli.…”
Section: Discussionmentioning
confidence: 97%
“…The olfactory perception in insects as well as other animals is generally dose-dependent. Dose beyond the threshold range, either too high or too low, will lead to a decrease in response [81]. Thus, the up-regulation induced by low-dose EBF, i.e., 40 ng, suggested that AgifOBP9 was associated with the high sensitivity of aphidius to EBF.…”
Section: Screening For Ebf-binding Proteinsmentioning
confidence: 99%
“…By analyzing the levels of JA and SA in ir- lrr rice and WT plants after SSB attack and mechanical damage, it can be concluded that OsLRR-RLK1 does not regulate the production of trauma-induced JA, JA-Ile, and SA in the absence of SSB attack [ 52 ]. Healthy rice plants were exposed to SSB-induced rice volatiles, and two JA signaling genes ( DOX2 and LOX8 ) were directly induced, resulting in a significant increase in JA accumulation [ 79 ]. The absence of OM64 in rice stimulates SSB-induced JA biosynthesis and response, enhancing the resistance of rice to the SSB [ 61 ].…”
Section: Defense Strategies Of Rice Against the Herbivorous Insect ...mentioning
confidence: 99%
“…When rice is attacked by the SSB, it can release a significant amount of (Z)-3-hexene-1-ol, which serves as an attractant for natural enemy parasitic wasps that parasitize SSB larvae. Similarly, other substances emitted by rice, such as linalool (terpenoids) or ethyl benzoate, methyl salicylate-4, 8-dimethyl-1, 3, 7-nonanetriene (DMNT), can also attract the arrival of parasitic wasps, thereby participating in the defense of rice against the SSB [ 79 , 80 ].…”
Section: Defense Strategies Of Rice Against the Herbivorous Insect ...mentioning
confidence: 99%
See 1 more Smart Citation